Чисельний аналіз температури стінки підземного каналу при спалюванні вугільного пилу - Лозинський В. Г. (НТУ "ДП", 2024)
Мета. Визначення оптимального підходу до оцінки температурних характеристик стінки каналу та його аналіз при чисельному моделюванні горіння вугільного пилу. Purpose. To determine the optimal approach for evaluating the temperature characteristics of the channel wall and analyze them in numerical modeling of pulverized coal combustion.
Numerical analysis of wall temperature in underground channel during pulverized coal combustion modeling
Keywords: комп’ютерне моделювання; горіння вугільного пилу; температура стінки; теплопередача; когазифікація; computational modeling; pulverized coal combustion; wall temperature; heat transfer; cogasification